2014
DOI: 10.1080/07294360.2014.934336
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and cognitive load in the flipped classroom: definition, rationale and a call for research

Abstract: terminology is new, some of the approaches being labelled 'flipped' are actually much older. In this paper we provide a catch-all definition for the flipped classroom, and attempt to retrofit it with a pedagogical rationale, which we articulate through six testable propositions. These propositions provide a potential agenda for research about flipped approaches and form the structure of our investigation. We construct a theoretical argument that flipped approaches might improve student motivation, and help man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
992
1
96

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,370 publications
(1,115 citation statements)
references
References 43 publications
26
992
1
96
Order By: Relevance
“…This suggests that the students are engaged with the flipped learning model and have actively participated in their learning, as they are reviewing the online material. The fact that they engage with the material in multiple bursts of brief timescales suggests a preference to learn material in small packages, which, as suggested by Abeysekera and Dawson [24], would reduce and spread cognitive load and provide time for reflection. Figure 2d shows the differences in the attendance at the flipped and non-flipped classes.…”
Section: Student Engagement With Flipped Learningmentioning
confidence: 98%
“…This suggests that the students are engaged with the flipped learning model and have actively participated in their learning, as they are reviewing the online material. The fact that they engage with the material in multiple bursts of brief timescales suggests a preference to learn material in small packages, which, as suggested by Abeysekera and Dawson [24], would reduce and spread cognitive load and provide time for reflection. Figure 2d shows the differences in the attendance at the flipped and non-flipped classes.…”
Section: Student Engagement With Flipped Learningmentioning
confidence: 98%
“…An increase in the popularity of flipped learning studies has been seen in recent years (Abeysekera & Dawson, 2015;Lo, Lie, & Hew, 2018;. Yarbro, Arfstrom, McKnight and McKnight (2014)'s summary of recent research on flipped learning showed how widely flipped learning has become embedded in most disciplines, including foreign languages, and widely used in higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in a quasi-experimental study, Touchton (2015) found statistically significant advantages to the flipped classroom including higher grades, greater student interest in the subject, and student perceptions of learning increasing or "as more relevant" relative to traditional classes. Despite the small empirical base, Abeysekera and Dawson (2015) argue that the case for flipped instruction is supported by evidence in related areas of research on active learning, self-paced learning, and issues related to cognitive load and motivation.…”
Section: Introductionmentioning
confidence: 99%
“…These two elements match Abeysekera and Dawson's (2015) conceptual review of the flipped classroom approach. Ultimately, it is a "set of pedagogical approaches that (1) move most information-transmission teaching out of class, (2) use class time for learning activities that are active and social, and (3) require students to complete pre-and/or post-class activities to fully benefit from in-class work" (Abeysekera & Dawson, 2015, p. 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation